Program “Bandung Menjawab” sebagai Strategi Komunikasi - Vickia Zairacantika; Riza Hernawati (UNISBA Press, 2023)
Abstract. Dinas Komunikasi dan Informatika (Diskominfo) Bandung City functions as a platform to communicate messages to the public. Diskominfo Bandung City develops one of its flagship programs,